Divergent migration within lake sturgeon (Acipenser fulvescens) populations: Multiple distinct patterns exist across an unrestricted migration corridor. (5th December 2017) - Kessel, Steven T.; Hondorp, Darryl W.; Holbrook, Christopher M.; Boase, James C.; Chiotti, Justin A.; Thomas, Michael V.; Wills, Todd C.; Roseman, Edward F.; Drouin, Richard; Krueger, Charles C.
Abstract: Population structure, distribution, abundance and dispersal arguably underpin the entire field of animal ecology, with consequences for regional species persistence, and provision of ecosystem services. Divergent migration behaviours among individuals or among populations are an important aspect of the ecology of highly mobile animals, allowing populations to exploit spatially or temporally distributed food and space resources. This study investigated the spatial ecology of lake sturgeon ( Acipenser fulvescens ) within the barrier free Huron‐Erie Corridor (HEC), which connects Lake Huron and Lake Erie of the North American Laurentian Great Lakes. Over 6 years (2011–2016), movements of 268 lake sturgeon in the HEC were continuously monitored across the Great Lakes using acoustic telemetry (10 years battery life acoustic transmitters). Five distinct migration behaviours were identified with hierarchical cluster analysis, based on the phenology and duration of river and lake use. Lake sturgeon in the HEC were found to contain a high level of intraspecific divergent migration, including partial migration with the existence of residents. Specific behaviours included year‐round river residency and multiple lake‐migrant behaviours that involved movements between lakes and rivers. Over 85% of individuals were assigned to migration behaviours as movements were consistently repeated over the study, which suggested migration behaviours were consistent and persistent in lake sturgeon. Differential use of specific rivers or lakes by acoustic‐tagged lake sturgeon further subdivided individuals into 14 "contingents" (spatiotemporally segregated subgroups). Contingents associated with one river (Detroit or St. Clair) were rarely detected in the other river, which confirmed that lake sturgeon in the Detroit and St. Clair represent two semi‐independent populations that could require separate management consideration for their conservation. The distribution of migration behaviours did not vary between populations, sexes, body size or among release locations, which indicated that intrapopulation variability in migratory behaviour is a general feature of the spatial ecology of lake sturgeon in unfragmented landscapes. Abstract : The study revealed considerable divergent migration within lake sturgeon populations across an unrestricted migration corridor. This highlights the level of migration behaviour variability fish will express in unfragmented landscapes.